Nature's wrath ; Home in Berlin ; Golden opportunity [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1991)
Probe looks into illegal logging as one of the main causes of destruction in Ormoc, Leyte; interviews with two Filipino jazz musicians about their life in Berlin and the atmosphere it provides their music; prospects of our country in the upcoming Games in December, 1991.
Nature's wrath (13 min.) -- Home in Berlin (12 min.) -- Golden opportunity (14 min.)
VHS.
Keywords: Del Rosario, Conrado -- Interviews; Southeast Asian Games (16th : 1991 : Philippines); Natural disasters -- Philippines -- Leyte; Disaster victims -- Philippines -- Leyte; Typhoons -- Philippines -- Leyte; Jazz, musicians, Filipino; Athletes -- PhilippinesxTraining; Sports -- Competitions